PERMAINAN PERAN (ROLE PLAY) UNTUK PEMBELAJARAN SHALAT - Sayed Fachrurrazi; Saiful Afwadi (TECHSI - Jurnal Teknik Informatika, 2013)
Many computer users pay more attention upon computer games, using this kind of computer features make the user able to stay long in fron of computer. The implementation of "Permainan Peran (Role Play) Untuk Pembelajaran Shalat" is one effort to follow the trend, with one hope the religious application have their own place in computer users mind. Thepattern of this Shalat learning application can generate interactive image dan sound, they can motivate and boast the spirit the users in learning shalat. It can help users to keep a close watch and frequently memorize the text to read in shalat while seing the picture of body movement as well even without the guidance of teacher.This application is not such as other game application which focuses on speed, but it stresses more on learning/memorizing the reciting and understanding the movement in shalat.